Combined Dominance and Average Algorithms for Spectrum Sharing in Cognitive Radio Networks (Al-Mansour Journal, 2022)
Cognitive radio networks (CRNs) are networks of nodes equipped with cognitive radios that can optimize performance automatically by changing its behavior to adapt to the environment. The Cognitive radio is a kind of two-way radio that automatically changes its transmission or reception parameter this alteration of parameters is based on the active monitoring of several factors in the external and internal radio environment, such as radio frequency spectrum, user behavior and network state the optimizes that use of available radio-frequency (RF) spectrum while minimizing interference to other users. This paper presents a major functionality in cognitive radio network (spectrum sensing and sharing) the idea of spectrum sharing for the participation of more than one operator uses one channel at the same time will be explained, taking in consideration the different types of sharing techniques using (distributed sharing), finally we modeling our work using game theory based on reduction through dominance and average algorithm through using graphic user interface in Matlab program. Simulations are used to study the performance of our proposed algorithm and demonstrate its effectiveness in terms of improving the overall network throughput, reducing the average transmission power and provide efficient bandwidth sharing. In this research represent the game theory and provides comprehensive treatment for it, with cognitive radio networks applications, which helps in design and efficient in the future of network by self-enforcing and distributed spectrum sharing schemes.
Keywords: cognitive radio network; game theory; spectrum sharing, QoS